ANALYSIS OF THE MOTIVATION LEVEL OF CONSTRUCTION PROJECT WORKERS DURING THE COVID-19 PANDEMIC BASED ON MASLOW'S THEORY USING THE BAYESIAN BELIEF NETWORK METHOD - Mirnayani; Lily Kholida (Jurnal Infrastruktur, 2022)
Labor productivity is a very important factor in construction because it will affect the successful implementation of a construction project. Workers (labor) are human resources who are directly involved in construction projects from beginning to end and have a major influence on management in them. Worker motivation affects the productivity of workers, while the efforts made by workers are the physical embodiment of motivation. The higher the motivation of the worker, the greater the effort he makes. Maslow's theory is the basis of the theory of human needs. The emergence of the Covid-19 pandemic has made changes to life due to the new policies in force. This research will use a quantitative approach using the Bayesian Belief Network (BBN). The results showed that the percentage of the large motivation of construction project workers at the Jakarta Internasional Stadium project during the Covid-19 pandemic was 72.90 good and 27.10 bad. These results can be used as consideration for relevant agencies to carry out alternative strategies to increase worker motivation during the Covid-19 pandemic, so that worker productivity remains high.